2006
DOI: 10.1177/1090198105285784
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Multicomponent Professional Development Training on the Beliefs and Behaviors of Community Health Educators Concerning Food Irradiation

Abstract: Beliefs have a significant effect on the health behaviors of individuals and educators; however, they can be difficult to change. The purpose of this study was to determine if exposing community health educators, specifically family and consumer sciences county extension educators, to a multicomponent professional development training on food irradiation could change their beliefs and behaviors. This study compared the food irradiation beliefs and educational programming of educators who participated in a prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Our results, based on PMT, explain a new outcome, consumer acceptance of meat irradiation, and found that this theory could indeed be applied to predict consumer willingness to buy irradiated meat. Our results also confirmed findings of the consumer psychology literature that emphasize the importance of the perceived safety, risks, and benefits of food processing technologies in understanding consumer acceptance of these technologies (Brown et al., ; Cope et al., ; Grunert, ; Thompson & Knight, ). Moreover, these results provide a number of the potential targets for future interventions aimed at improving acceptance of meat irradiation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results, based on PMT, explain a new outcome, consumer acceptance of meat irradiation, and found that this theory could indeed be applied to predict consumer willingness to buy irradiated meat. Our results also confirmed findings of the consumer psychology literature that emphasize the importance of the perceived safety, risks, and benefits of food processing technologies in understanding consumer acceptance of these technologies (Brown et al., ; Cope et al., ; Grunert, ; Thompson & Knight, ). Moreover, these results provide a number of the potential targets for future interventions aimed at improving acceptance of meat irradiation.…”
Section: Discussionsupporting
confidence: 88%
“…There are a number of difficulties with such proposals, not the least of which is the possibility that the proposed term may be perceived as deceptive. Instead, education about the irradiation process and the safety of food irradiation may help positively influence the public's attitude as evidenced by previous studies (Fox, 2002;Fox et al, 2002;Nayga Jr, Woodward, & Aiew, 2006;Thompson & Knight, 2006;Thompson, Ribera, Wingenbach, & Vestal, 2007). Further, increasing the public's awareness of the risks associated with foodborne illness may lead to greater acceptance of measures to combat foodborne contamination.…”
Section: Discussionmentioning
confidence: 98%
“…Calls were made for a co‐ordinated, balanced public education and information programme , to raise public awareness of the benefits, costs and risks of FI . Research has demonstrated that short video presentations, informational brochures , newspapers and government flyers were effective ways to transfer information about FI to the public; endorsement of FI by health professionals was also shown to increase acceptability .…”
Section: Awareness and Knowledgementioning
confidence: 99%
“…Recent research with community‐based nutrition and health educators, specifically family and consumer sciences county extension educators, indicates their perceived understanding about food irradiation and its safety influenced the amount of education they provided to clients on this topic (Thompson and Knight 2006a, 2006b). In addition, the amount of teaching experience of these educators influenced their beliefs toward the safety of food irradiation (Thompson and Knight 2006a).…”
Section: Introductionmentioning
confidence: 99%